The co-production of campus safety and security: a case study at the University of Georgia. (March 2016) - Williams, Brian N.; LePere-Schloop, Megan; Silk, P. Daniel; Hebdon, Alexandra
Campus safety and security is a salient issue and an area of increasing concern facing educational institutions in the United States. Yet little is known regarding ongoing efforts and resulting difficulties to co-produce campus safety and security. This article contributes to the literature on co-production by examining student and campus police officer perceptions of the professional–service user relationship in the context of campus safety and security. Findings suggest that demographic and contextual factors shape user and professional perceptions of their relationship in different ways, and that these perceptual differences affect efforts to co-deliver services. Points for practitioners: This article describes the views of university police personnel and students regarding the co-production of safety and security on a research university campus in the United States. Data gleaned from the research illustrates that while police officers and students may have differing views of one another and their roles in co-production, they agree that public safety would be served by opportunities for police and students to meet one another and have personal interaction outside of formal, law enforcement-driven situations. This suggests the value of well-developed engagement strategies, as well as the potential benefit of harnessing 'teachable moments' during which police and the student population can learn about one another.